Assessing correlation between Leadership styles of nurse managers and nurses’ intention to stay - Kaveh, jalil; Ruzbeh, alimostafa; ahmadi, sorya (Advances in Nursing & Midwifery, 2012)
Abstract Background and aim: Health care organizations spend huge amount asset in attracting, developing, and maintaining an effective workforce. The purpose of this study was to examine the correlation between leadership styles of nurse managers and nurses’ intent to stay at work in specialized wards in Imam Hossien and Moddaress teaching hospitals ,in Tehran,Iran .. Material and methods This study used a descriptive correlational design. The sample of the study consisted of 148 nurses in specialized wards of Imam Hossien and Moddarss teaching hospitals in Tehran .Data were collected by a demographic form, Management style measurement questionnaire an intention to leave questionnaire. The management style questionnaire constituted of a four -point Likert scale with 24 statements , and intention to stay questionnaire consisted of 21 items with a four-point likert scale. The validity of these questionnaires were determined by content validity . Reliability of questionnaires were assessed by internal consistency measuring Alpha Cronbach , Cronbach’s alpha was0.87 and 0.94 for intention to stay and leadership style questionnaires respectively. Data were analyzed by SPSS software Findings respondents were predominantly female and consist of 83/9% females and 16/9% males. The mean age was 31/5±6 years. There was no significant correlation between the imperiouse-imperious ,propitious-advisory leadership styles of nurse managers and nurses’ intention to stay. There was a significant correlation between partnership management style of nurse managers and nurses’ intention to stay . Key words: Leadership styles, Imperative, Imperative benevolent, consultive, partnership, Intention to stay